2004
DOI: 10.2527/2004.8241108x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soybean variety and processing on growth performance of young chicks and pigs1

Abstract: The objective of this study was to determine whether soybeans without the Kunitz trypsin inhibitor and lectins could be fed effectively to young chicks and pigs. Specifically, we compared the growth performance of chicks and pigs fed diets containing modified soybeans: Kunitz trypsin inhibitor-free (KF), lectin-free (LF), lectin and Kunitz trypsin inhibitor-free (LFKF), conventional soybeans (CSB), and commercially obtained, dehulled, solvent-extracted soybean meal (SBM). A 7-d chick experiment was conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 18 publications
1
15
0
2
Order By: Relevance
“…Plant proteins contain wide variety of compounds, some with anti-nutritional properties, severely limiting their inclusion in aquaculture feed (Chowdhury, Martie & Bureau 2015b). For example, high level of heat-stable anti-nutrients, such as antigenic proteins and lectin in soybeam meal (Thiessen, Campbell & Adelizi 2003;Palacios, Easter, Soltwedel, Parsons, Douglas, Hymowitz & Pettigrew 2004) and phytic acid, glucosinolates and erucic acid in rapeseed or Indian mustard meal or canola meal (Chowdhury et al 2015b). A major objective of the use of protease in animal feed is to improve utilization of the alternative dietary protein sources.…”
Section: Introductionmentioning
confidence: 99%
“…Plant proteins contain wide variety of compounds, some with anti-nutritional properties, severely limiting their inclusion in aquaculture feed (Chowdhury, Martie & Bureau 2015b). For example, high level of heat-stable anti-nutrients, such as antigenic proteins and lectin in soybeam meal (Thiessen, Campbell & Adelizi 2003;Palacios, Easter, Soltwedel, Parsons, Douglas, Hymowitz & Pettigrew 2004) and phytic acid, glucosinolates and erucic acid in rapeseed or Indian mustard meal or canola meal (Chowdhury et al 2015b). A major objective of the use of protease in animal feed is to improve utilization of the alternative dietary protein sources.…”
Section: Introductionmentioning
confidence: 99%
“…However, the IVID of DM in SBMW was slightly greater than the reported value (Navarro et al, 2018) while the IVID of CP and IVTTD of DM in SBMW were close to the reported values (Boisen and Fernández, 1995;Navarro et al, 2018). The nutrient concentrations in Soybean Meal (SBM) are often variable (Douglas et al, 2000) depending on the genotype (Palacios et al, 2004) and the growing environment (van Kempen et al, 2002). Heat processing may also affect the nutrient concentrations and bioavailability of nutrients in SBM (Goebel and Stein, 2011).…”
Section: Discussionmentioning
confidence: 63%
“…Vidljive posledice su zaostajanje u rastu i razvoju, što je izraženije kod mlađih organizama . Zrno soje bez KTI može da se koristi u ishrani odraslih nepreživara dok bi za ishranu mladih životinja trebalo da bude eliminisan i lektin (Palacios, 2004) . Da bi zrno soje moglo da se koristi u ishrani domaćih životinja i ljudi, tripsin inhibitori se inaktiviraju najčešće procesima koji uključuju termičku obradu, zahtevaju veliki utrošak energije a dolazi i do denaturacije i pogoršanja svarljivosti korisnih proteina (Aviles-Gaxiola et al ., 2018) .…”
Section: Uvodunclassified